Separation of binary mixtures aromatic + aliphatic using ionic liquids: Influence of the structure of the ionic liquid, aromatic and aliphatic - Noélia Calvar (2011)
Binary mixtures of hydrocarbon + aromatic compounds are usually separated using conventional organic volatiles, and to avoid the use of these compounds, the ionic liquids are gaining importance to substitute them. To study the influence of the structure of the different compounds on the separation, we have carried out the liquid-liquid equilibrium of ternary systems containing binary mixtures of hydrocarbon + aromatic compounds and ionic liquids, namely hexane or heptane or cyclohexene + benzene + BMimMSO4, hexane or cyclohexane + benzene + BMimNTf2 and hexane + toluene + BMimNTf2 at 298.15 K and atmospheric pressure, and the obtained experimental data have been correlated using NRTL and UNIQUAC models. The comparison of the phase behavior of the different systems studied has allowed us to analyze the influence of the anion of the ionic liquid, the chain length of the aliphatic and the lack of substituent (side chain) in the aromatic compound on the phase equilibria and on the separation ability of these ionic liquids